2022
DOI: 10.1002/alz.12748
|View full text |Cite
|
Sign up to set email alerts
|

The AHEAD 3‐45 Study: Design of a prevention trial for Alzheimer's disease

Abstract: Introduction: The Alzheimer's disease (AD) continuum begins with a long asymptomatic or preclinical stage, during which amyloid beta (Aβ) is accumulating for more than a decade prior to widespread cortical tauopathy, neurodegeneration, and manifestation of clinical symptoms. The AHEAD 3-45 Study (BAN2401-G000-303) is testing whether intervention with lecanemab (BAN2401), a humanized immunoglobulin 1 (IgG1) monoclonal antibody that preferentially targets soluble aggregated Aβ, initiated during this asymptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…Amyloid PET scans with 11 C-Pittsburgh Compound B (or PiB) were obtained via previously described methods, and images were processed using the PET unified pipeline (PUP, https://github.com/ysu001/ PUP). 34,35 Briefly, dynamically acquired PET data were reconstructed into frames that underwent affine registration to correct for interframe motion.…”
Section: Positron Emission Tomography (Pet) Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Amyloid PET scans with 11 C-Pittsburgh Compound B (or PiB) were obtained via previously described methods, and images were processed using the PET unified pipeline (PUP, https://github.com/ysu001/ PUP). 34,35 Briefly, dynamically acquired PET data were reconstructed into frames that underwent affine registration to correct for interframe motion.…”
Section: Positron Emission Tomography (Pet) Imagingmentioning
confidence: 99%
“…Amyloid PET is well correlated with AD neuropathology, 5–7 and is often used as the reference standard for brain amyloidosis 8,9 . Amyloid PET positivity is also used as an enrollment criterion for clinical trials, including trials in cognitively normal individuals that are designed to prevent or slow AD symptom onset 10,11 . Multiple studies have demonstrated that amyloid plaques, as measured by PET, accumulate consistently across individuals during preclinical AD (when individuals are amyloid positive but cognitively normal), enabling staging of preclinical AD with continuous measures of amyloid PET 12–17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 16 The demand for biomarkers is likely to increase even more with the rising prospect of disease-modifying therapies for AD 17 - 21 and expansion of clinical trials evaluating investigational agents designed to prevent cognitive impairment in patients at high risk of developing dementia due to AD. 22 , 23 …”
Section: Ad Biomarkers In Clinical Practicementioning
confidence: 99%
“…4,16 The demand for biomarkers is likely to increase even more with the rising prospect of disease-modifying therapies for AD [17][18][19][20][21] and expansion of clinical trials evaluating investigational agents designed to prevent cognitive impairment in patients at high risk of developing dementia due to AD. 22,23 Established AD biomarkers include PET-neuroimaging and cerebrospinal fluid measures. However, PET-based measures are costly, are seldom covered by insurers, and require access to specialized neuroimaging infrastructure and expertise.…”
Section: Ad Biomarkers In Clinical Practicementioning
confidence: 99%